1997
DOI: 10.1002/(sici)1096-9861(19971215)389:2<277::aid-cne7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference and steroidal stimulation of galanin immunoreactivity in the ferret's dorsal preoptic area/anterior hypothalamus

Abstract: A sexually dimorphic male nucleus (MN) is seen in Nissl-stained sections from the dorsal preoptic area/anterior hypothalamus (dPOA/AH) of male, but not female, ferrets. We used immunohistochemical methods to determine whether particular neuropeptides are found in cells of the MN. A sexually dimorphic cluster of galanin-immunoreactive (IR) cells was found in the dPOA/AH of ferrets killed either on embryonic day (E) 38 or in adulthood. Significantly more galanin-IR cells were distributed in the MN and in other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 55 publications
1
14
1
Order By: Relevance
“…The function of galanin neurons in the human InM is not known, but animal experiments suggest that this area and its galanin neurons in particular may be involved in sexual and reproductive behavior (Swaab, 2003, 2004a). In the ferret the medial preoptic galanin neurons are activated during mating (Bakker et al, 2002), and the galanin production of the InM neurons of the ferret is activated by testosterone (Park et al, 1997). The SDN‐POA size in rats is positively correlated with the frequency of masculine sexual behavior, as well as with male preference for a female over a male (Houtsmuller et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of galanin neurons in the human InM is not known, but animal experiments suggest that this area and its galanin neurons in particular may be involved in sexual and reproductive behavior (Swaab, 2003, 2004a). In the ferret the medial preoptic galanin neurons are activated during mating (Bakker et al, 2002), and the galanin production of the InM neurons of the ferret is activated by testosterone (Park et al, 1997). The SDN‐POA size in rats is positively correlated with the frequency of masculine sexual behavior, as well as with male preference for a female over a male (Houtsmuller et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In the preoptic area of the ferret, a sexually dimorphic cell group was found that contained more galanin neurons in males than in females. The density of galanin neurons was reduced by castration and restored by testosterone treatment (Park et al, 1997). In the rat, large numbers of galanin neurons were found in the medial preoptic area, which decreased following gonadectomy in males and increased again after administration of either testosterone or estrogens in both sexes (Bloch et al, 1993, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone has been proposed to underlie the sex differences in atrophy associated with galanin-expressing neurons within the preoptic hypothalamic area (Garcia-Falgueras et al, 2011). In rodent studies, galanin neuronal density is reduced by castration and restored with testosterone treatment (Park et al, 1997). In human studies, both castrated men and male to female transsexual individuals have galanin-expressing neurons within the preoptic area of the hypothalamus reduced to a number similar to that observed in women (Garcia-Falgueras et al, 2011).…”
Section: What Are the Neurobiological Mechanisms Of Age-related Sleepmentioning
confidence: 99%
“…Using immunocytochemical methods, the neurochemical phenotype of neurones in the ferret's sexually dimorphic dmPOA/AH was determined (6). A striking sex difference was found in the distribution of galanin‐immunoreactive (IR) neurones: gonadally intact males in breeding condition had many more galanin‐IR neurones in the dmPOA/AH than gonadally intact, oestrous females.…”
mentioning
confidence: 99%
“…The sex difference in galanin‐IR in the dmPOA/AH did not result from sex differences in circulating testosterone levels; treatment with high doses of testosterone propionate (5 mg/kg) failed to augment the number of galanin‐IR neurones in adult, ovo‐hysterectomized females. However, prenatal treatment with testosterone propionate significantly increased numbers of galanin‐IR neurones in the dmPOA/AH of females up to the level seen in males, implying that the capacity of these dmPOA/AH cells to express galanin is sexually differentiated prenatally by testosterone and/or its oestrogenic metabolite in male ferrets (6). Sex differences in the distribution of galanin neurones in the POA/AH have also been described for several other species, including the teleost fish sailfin molly (7), the goldfish (8), the mouse (9), the rat (10) and the gerbil (11).…”
mentioning
confidence: 99%